2011
DOI: 10.4161/auto.7.12.17909
|View full text |Cite
|
Sign up to set email alerts
|

Ins(1,4,5)P3receptor-mediated Ca2+signaling and autophagy induction are interrelated

Abstract: Immunoprecipitation experiments showed that during starvation Beclin 1, released from Bcl-2, first bound with increasing efficiency to Ins(1,4,5)P 3 Rs; after reaching a maximal binding after 3 h, binding, however, decreased again. The interaction site of Beclin 1 was determined to be present in the N-terminal Ins(1,4,5)P 3 -binding domain of the Ins(1,4,5) P 3 R. The starvation-induced Ins(1,4,5)P 3 R sensitization was abolished in cells treated with BECN1 siRNA, but not with ATG5 siRNA, pointing toward an es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
153
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(156 citation statements)
references
References 71 publications
3
153
0
Order By: Relevance
“…In line with several studies demonstrating that alterations of calcium metabolism can induce autophagy (Decuypere et al, 2011(Decuypere et al, , 2013Ghislat et al, 2012), we also considered this mechanism in the present study. Although an increase in cytoplasmic calcium levels was observed in brain endothelial cells exposed to efavirenz, this increase did not result in stimulation of autophagy.…”
Section: Dysregulation Of Er Stress and Autophagy By Efavirenzsupporting
confidence: 50%
“…In line with several studies demonstrating that alterations of calcium metabolism can induce autophagy (Decuypere et al, 2011(Decuypere et al, , 2013Ghislat et al, 2012), we also considered this mechanism in the present study. Although an increase in cytoplasmic calcium levels was observed in brain endothelial cells exposed to efavirenz, this increase did not result in stimulation of autophagy.…”
Section: Dysregulation Of Er Stress and Autophagy By Efavirenzsupporting
confidence: 50%
“…IP 3 R1 knockdown increases LC3-II (lapidated microtubule-associated protein light chain 3, LC3, an index of autophagy) content without changing the amount of actin (Fig. 3A), consistent with previous reports (24)(25)(26)(27). Furthermore, we found that TG2 knockdown had the opposite effect (Fig.…”
Section: Resultssupporting
confidence: 82%
“…To examine the physiological role of this regulation in the cellular functions of IP 3 R1, we studied the role of TG2 and IP 3 R in autophagy. IP 3 R1 regulates autophagy (24)(25)(26)(27), and TG2 is also thought to regulate autophagy (50,51); however, the interplay between TG2 and IP 3 R1 in autophagy regulation has not been studied. We hypothesized that TG2 affects IP 3 R1-mediated autophagy regulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,65 Moreover, an additional study established that subjecting HeLa cells to short periods of starvation causes a prominent increase of the ER Ca 2+ -store content and enhances agonist-induced ER Ca 2+ release, resulting in autophagy. 66 A related study by Ghislat et al 67 found that starvation-induced autophagy proceeds via the CAMKK2-PRKAA-MTOR pathway.…”
Section: + As An Autophagy Suppressormentioning
confidence: 99%